Catastrophic health expenditure and impoverishment in households of persons with depression: a cross-sectional, comparative study in rural Ethiopia - Yohannes Hailemichael; Charlotte Hanlon; Kebede Tirfessa; Sumaiyah Docrat; Atalay Alem; Girmay Medhin; Crick Lund; Dan Chisholm; Abebaw Fekadu; Damen Hailemariam (BMC, 2019)
Abstract Background The extent of catastrophic health expenditure and impoverishment associated with depression in low-and middle-income countries is not known. The aim of this study was to estimate the incidence and intensity of catastrophic out-of-pocket (OOP) health expenditure, level of impoverishment and coping strategies used by households of persons with and without depression in a rural Ethiopian district. Methods A comparative cross-sectional survey was conducted, including 128 households of persons with depression and 129 households without. Depression screening was conducted using the Patient Health Questionnaire, nine item version (PHQ-9). People in the depression group were classified into high and low disability groups based on the median value on the World Health Organization Disability Assessment Schedule (WHODAS) polytomous summary score. Health expenditure greater than thresholds of 10 and 25% of total household consumption was used for the primary analyses. The poverty headcount, poverty gap and normalized poverty gap were estimated using retrospective recall of total household expenditure pre- and post-OOP payments for health care. Linear probability model using binreg command in STATA with rr option was used to estimate risk ratio for the occurrence of outcomes among households with and without depression based on level of disability. Results Catastrophic OOP payments at any threshold level for households with depression and high disability were higher than control households. At the 10% threshold level, 24.0% of households of persons with depression and high disability faced catastrophic payments compared with 15.3% for depression and low disability and 12.1% for control households (p = 0.041). Depression and high disability level was an independent predictor of catastrophic OOP payments: RR 2.1; 95% CI:1.1, 4.6. An estimated 5.8% of households of persons with depression and high disability were pushed into poverty because of paying for health care compared with 3.5% for households of persons with depression and low disability and 2.3% for control households (p = 0.039). Conclusions Households of people with depression and high disability were more likely to face catastrophic expenditures and impoverishment from OOP payments. Financial protection interventions through prepayment schemes, exemptions and fee waiver strategies need to target households of persons with depression.